A Pictorial history of African Americans - Hughes, Langston, 1902-1967. (New York : Crown Publishers, 1995)
A history of African Americans from the origins of slavery in the colonies to the present day, with reproductions of many illustrations, photographs, and historical documents.
The peculiar institution -- Free men of color -- The north star -- Up from slavery -- The souls of black folk -- The new Negro -- Searching for freedom -- The range of resistance -- Sharing the power -- Afro-America coming into its own.
Includes index.
"Sixth revised edition of a pictorial history of the Negro in America."
Keywords: African Americans -- History; African Americans -- History -- Pictorial works